De l’émancipation à l’institutionnalisation : santé sexuelle et droits sexuels - Alain Giami (Genre, Sexualité et Société)
At the start of the 1970s, “sexual health” made headway in the World Health Organization; and UN organizations started considering that questions related to family planning and violence against women were human rights issues. The convergence of these two lines of thought led to proposals on sexual rights with the objective of validating sexual and reproductive health recommendations and campaigns against the discrimination of LGBT persons. The paper proposes a detailed analysis of the gradual emergence of questions related to nonreproductive sexualities in the fields of human rights and international health and the institutionalization of issues related to sexual rights. It aims at understanding how the association between health and Human Rights represents a new form of sexual morality.